Unraveling the Dynamics of Family, Anxiety, and Depression Among Chinese Vocational Students [Letter] - Prasetio B; Supardi E; Fajri MA (Psychology Research and Behavior Management)
Bayu Prasetio,1 Endang Supardi,1 Muthia Atika Fajri2 1Department of Economics Education, Universitas Pendidikan Indonesia, Bandung, Indonesia; 2Department of Early Childhood Education, Universitas Pendidikan Indonesia, Bandung, IndonesiaCorrespondence: Endang Supardi, Department of Economics Education, Universitas Pendidikan Indonesia, Bandung, Indonesia, Email endang-supardi@upi.edu